2012
DOI: 10.1186/1741-7015-10-56
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of transplanted placental mesenchymal stem cells in treating Chinese miniature pigs with acute liver failure

Abstract: BackgroundStem cell-based therapy to treat liver diseases is a focus of current research worldwide. So far, most such studies depend on rodent hepatic failure models. The purpose of this study was to isolate mesenchymal stem cells from human placenta (hPMSCs) and determine their therapeutic potential for treating Chinese experimental miniature pigs with acute liver failure (ALF).MethodshPMSCs were isolated and analyzed for their purity and differentiation potential before being employed as the donor cells for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 60 publications
5
88
0
1
Order By: Relevance
“…Some studies have attempted to demonstrate hPMSCs homing to the liver and differentiating into normal hepatocytes; hPMSCs can also potentially activate and support the differentiation and proliferation of liver progenitor cells. Differentiated hepatic cells are capable of secreting multiple cytokines and growth factors to reduce inflammation and angiogenesis and accelerate restoration of the liver [2][3][4]. However, there is no convincing evidence that the biological characteristics of hPMSCs, including homing, differentiation and secretion, are responsible for their therapeutic effects in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have attempted to demonstrate hPMSCs homing to the liver and differentiating into normal hepatocytes; hPMSCs can also potentially activate and support the differentiation and proliferation of liver progenitor cells. Differentiated hepatic cells are capable of secreting multiple cytokines and growth factors to reduce inflammation and angiogenesis and accelerate restoration of the liver [2][3][4]. However, there is no convincing evidence that the biological characteristics of hPMSCs, including homing, differentiation and secretion, are responsible for their therapeutic effects in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…2013-272). hPMSCs were collected from fresh human placentas and prepared as described previously [3]. The day before transduction, hPMSCs (passage 3) were cultured in a 6-well plate at a density of 1 × 10 4 /cm 2 in special medium (MesenCult ® Human Basal Medium plus MesenCult Human Supplement; STEMCELL Technologies Inc., Vancouver, BC, Canada).…”
Section: Gfp Transductionmentioning
confidence: 99%
“…The transplanted cells contributed to liver regeneration and transdifferentiation into hepatocytes in recipient liver which accounted for 30% of the total hepatocytes. Moreover, animals in transplanted group survived for more than 6 months while control group died within 96 hours [68]. Similarly, Cao et al also demonstrated the therapeutic potential of transplanted human placenta-derived MSCs (PD-MSCs) in pig with D-galactosamine-induced acute liver failure.…”
Section: In Vivo Studies Of Mscs In Liver Diseasesmentioning
confidence: 93%
“…One of the important points highlighted by the authors was the comparative analysis between two different ways for cellular administration: jugular vein and portal vein. The authors clearly showed that infusion through portal vein resulted in better clinical parameters than jugular vein one [141].…”
Section: Placenta-derived Stem Cellsmentioning
confidence: 99%